2021
DOI: 10.3390/ani11123464
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reduced Space Allowance and Heat Stress on Behavior and Eye Temperature in Unweaned Lambs: A Pilot Study

Abstract: Current European animal transportation law contains only a few and vague indications concerning how to move lambs of less than 26 kg. Moreover, little information is available in the literature about factors affecting these lambs’ welfare. We investigated the effect of space allowance and ambient temperature on the welfare of unweaned Lacaune lambs during a simulation of long-distance transportation (19 h). Three groups of lambs (N = 130) were housed in equally sized pens for 19 h, Control (C; n = 39; 0.27 m2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 65 publications
1
12
2
Order By: Relevance
“…The neck forward behavior was positively associated with the stretching behavior. Stretching is usually categorized as a comfort behavior for broilers 30 , but it could also be used when the animal needs to relax stress-related tension in their muscles 31 , 32 or as an adaptive strategy for dealing with unknown contexts 33 . Neck forward and stretching were eventually considered social avoidance behaviors, although they could be ambivalent and thus require further study, case-by-case assessment, and perhaps a better description in the ethogram.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neck forward behavior was positively associated with the stretching behavior. Stretching is usually categorized as a comfort behavior for broilers 30 , but it could also be used when the animal needs to relax stress-related tension in their muscles 31 , 32 or as an adaptive strategy for dealing with unknown contexts 33 . Neck forward and stretching were eventually considered social avoidance behaviors, although they could be ambivalent and thus require further study, case-by-case assessment, and perhaps a better description in the ethogram.…”
Section: Discussionmentioning
confidence: 99%
“…These trials were performed in the hottest season; thus, the geese's behavioral differences during the day could also depend on the fact that animals preferred to carry out active behaviors during the cooler hours (morning), while in the hottest hours (afternoon), they engaged in static activities. Active behaviors cause an increase in metabolism and body temperature 38 , whereas static behavior, such as roosting, is considered adaptative behavior to promote heat dissipation 31 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient horizontal space (space allowance): At some stage of the journey, sheep may need to lie down either when the vehicle is in motion or stationary (Menchetti et al, 2021).…”
Section: Iv) Resting Problemsmentioning
confidence: 99%
“…Menchetti et al. (2021) reported that lambs of 25 kg, that were not transported, had a greater frequency of trampling and aggressive behaviour when kept at a k‐value of 0.026 than at a k‐value of 0.033.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation